Evaluation and Classification of Action on the Policy of Sustainable Livestock Development in Pasuruan Regency East Java - Brehaspati, Eka Wara; Riniwati, Harsuko; Ciptadi, Gatot; Putra, Fadillah (Jurnal Pembangunan dan Alam Lestari, 2025)
Livestock is an integral part of agriculture, contributing significantly to many developing countries' rural economies and socio-economic development. Livestock is an important part of the national economic potential that can increase the added value of Indonesia's agricultural sector. The livestock sector has a very good market opportunity because the domestic market will continue to increase along with the rapidly growing population. Business actors in the livestock sector have made several efforts in developing the livestock sector, one of which is in the form of environmental-based animal husbandry education tours. The purpose of this research is to analyze the best action program for the development of sustainable livestock tourism. The action programs are ecotourism, Livestock, infrastructure, product quality, Information and Communication Technology, education and training, and formal education. Data were collected from experts in the field of livestock tourism. Data is analyzed using multi-policy. The analysis results show that the ecotourism action program is the best, with a mean is 18.8 and the smallest standard error. Research advice is to formulate appropriate policies that can realize ecotourism in Regional Technical Implementation Unit Pasuruan Regency.